Coordinating capital flows and macroprudential tools for price and financial stability - Sihombing, Tohap Parulian; Nopeline, Nancy (Edelweiss Applied Science and Technology, 2025)
Financial stability and low inflation remain central objectives for emerging economies subject to large and volatile capital flows. This paper evaluates how macroprudential regulations and conventional monetary policy interact to support price and financial stability in Indonesia. Using quarterly data from Q1 2005 to Q4 2021, we estimate a Structural Vector Autoregression (SVAR) model and derive impulse response functions (IRFs) and forecast-error variance decompositions (FEVDs) to measure policy shock dynamics. Our findings indicate that a one-standard-deviation increase in the policy interest rate lowers inflation by 0.4 percentage points two quarters after the shock and reduces exchange-rate volatility by up to 1.2% at its peak in quarter 3. Variance decomposition attributes 21.2% and 22.5% of inflation variability to monetary policy shocks in the short and long run, respectively, while capital inflows explain 4.2% and 11.5% over the same horizons. Complementary macroprudential instruments, such as countercyclical capital buffers, further dampen credit growth and enhance monetary transmission. These empirical results underscore that a coordinated policy mix bolsters the resilience of Indonesia’s financial system against external disturbances. The study provides actionable insights for calibrating monetary and macroprudential tools within an integrated policy framework.